Analisis Jasa Penitipan Motor Tanpa Jaminan Ditinjau Dari Hadits Riwayat Abu Daud Dan Pasal 1714 KUHPerdata - Raga Bahira Albantani; Tajul Arifin (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Motorcycle storage without collateral is a service increasingly popular in dense urban communities. However, it raises various legal questions regarding the responsibilities and risks involved, both for service providers and motorcycle owners. In this study, we analyze the motorcycle storage service without collateral from the perspectives of Islamic law and civil law. From the perspective of Islamic law, the sayings of Prophet Muhammad emphasize the importance of maintaining trust in every transaction, while civil law provides a structured framework through Article 1714 of the Indonesian Civil Code. Although there are differences in approach between these perspectives, there are also important points of convergence regarding the maintenance of trust and justice in every transaction. The implication of this analysis is the importance of understanding and respecting legal principles, both from the perspective of Islamic law and civil law, in providing and using motorcycle storage services without collateral.